Optimal Contracting with Private Knowledge of Wealth and Ability - Lewis, T. R.; Sappington, D. E. M. (Review of Economic Studies, 2001)
We examine the optimal design of contracts when an agent is privately informed about his wealth, his ability, and his effort supply. We find that the agent's wealth and ability act as perfect complements in determining the power of the incentive scheme under which he operates. Only if his ability and his wealth both increase can an agent be assured of operating under a more powerful scheme. Consequently, severe under-utilization of wealth and ability arise in equilibrium.